2016
DOI: 10.1021/acs.biomac.5b01728
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Thermoresponsive Microgel Coatings for Noninvasive Processing of Adherent Cells

Abstract: Cultivation of adherently growing cells in artificial environments is of utmost importance in medicine and biotechnology to accomplish in vitro drug screening or to investigate disease mechanisms. Precise cell manipulation, like localized control over adhesion, is required to expand cells, to establish cell models for novel therapies and to perform noninvasive cell experiments. To this end, we developed a method of gentle, local lift-off of mammalian cells using polymer surfaces, which are reversibly and repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 23 publications
1
69
0
Order By: Relevance
“…Uhlig et al designed artificial surfaces patterned with thermoresponsive microgels using nanodispensing and microcontact printing (µCP) for controlled adhesion, and cell growth of L929 mouse fibroblasts, and CHO‐K1 epithelial cells . Cell attachment, growth, and detachment from the surface were controlled by tuning the degree of swelling and elastic modulus of microgels.…”
Section: Microgels For Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Uhlig et al designed artificial surfaces patterned with thermoresponsive microgels using nanodispensing and microcontact printing (µCP) for controlled adhesion, and cell growth of L929 mouse fibroblasts, and CHO‐K1 epithelial cells . Cell attachment, growth, and detachment from the surface were controlled by tuning the degree of swelling and elastic modulus of microgels.…”
Section: Microgels For Tissue Engineeringmentioning
confidence: 99%
“…These surfaces could be switched between a cell‐attractive and a cell‐repellent state and the grown cells could be used to perform noninvasive cell experiments. It was observed that the cells were well spread on the surface at 37 °C, while high water content, increased repulsive interactions, and unfavorable modulus at 25 °C lead to their complete detachment ( Figure ) …”
Section: Microgels For Tissue Engineeringmentioning
confidence: 99%
“…In addition, above the LCST, the microgels are hydrophobic and show a smooth surface whereas below the LCST the surface is fuzzy and the polymers are hydrated . The temperature‐control over hydrophobicity, surface structure, and stiffness was successfully used to construct microgel coatings for switchable cell culture surfaces . However, these materials do not specifically bind certain cells or bacteria but are quite promiscuous and would bind to virtually any protein, which makes it difficult to control their adhesive properties.…”
Section: Switchable Carbohydrate Presenting Scaffoldsmentioning
confidence: 99%
“…In previous work, poly( N ‐isopropylacrylamide)‐based microgels have been used as novel thermoresponsive coatings to harvest cell/cell sheets by temperature stimulation . These work mainly focused on cell detachment behavior using the microgel monolayer, the effect of the thermoresponsive microgels distribution on cell attachment, morphology, activity, and detachment has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%